YOUTH AS FRONTLINE PEACEBUILDERS: INTEGRATING INTERGROUP CONTACT AND SOCIAL CAPITAL TO PREVENT RELIGIOUS CONFLICT IN CENTRAL JAVA - Nur Rois; Rahmawati, Lila; Mahsun; Fadhillah, Iman (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2025)
Religious conflict in Central Java continues to manifest through social tensions, rejection of houses of worship, and identity‑based disputes. Although previous studies have examined religious moderation and state policy, limited research has systematically analyzed how youth organizations develop preventive peacebuilding strategies at the local level. This study addresses this gap by examining youth‑led initiatives through the combined lenses of Intergroup Contact Theory and Social Capital Theory. This study employed a descriptive qualitative design using multiple case studies in Temanggung, Purworejo, Kudus, Jepara, and Semarang, Central Java. Data were collected from interviews, observations of interfaith activities and documentation from civil society organizations. Thematic analysis was used to identify cross‑case patterns of youth intervention. The findings indicate three key results. First, youth act as social mediators who facilitate intergroup dialogue and de‑escalate tensions in cases involving blasphemy accusations, inter‑organizational disputes, and contested burial practices. Second, youth initiatives such as Peace School, Peace Cottage, and interfaith youth forums strengthen bridging social capital and create structured intergroup contact that reduces prejudice. Third, youth networks contribute to policy shifts at the district level, including more inclusive procedures for worship‑house permits. These findings demonstrate that youth are central actors in grassroots conflict prevention, not merely beneficiaries of state‑led moderation programs. The study concludes that integrating intergroup contact and social capital provides a robust framework for understanding youth‑based peacebuilding and recommends that local governments institutionalize youth participation in early warning and conflict‑prevention mechanisms. Abstrak Konflik keagamaan di Jawa Tengah terus muncul melalui ketegangan sosial, penolakan rumah ibadah, dan sengketa berbasis identitas. Meskipun berbagai penelitian telah membahas moderasi beragama dan kebijakan negara, kajian yang secara sistematis menganalisis bagaimana organisasi kepemudaan mengembangkan strategi pembangunan perdamaian yang bersifat preventif di tingkat lokal masih terbatas. Studi ini mengisi kesenjangan tersebut dengan menelaah inisiatif pemuda melalui pendekatan gabungan Teori Kontak Antarkelompok dan Teori Modal Sosial. Penelitian ini menggunakan desain kualitatif deskriptif dengan studi multi‑kasus di Temanggung, Purworejo, Kudus, Jepara, dan Semarang. Data dikumpulkan melalui wawancara, observasi kegiatan lintas iman, serta dokumentasi dari organisasi masyarakat sipil. Analisis tematik digunakan untuk mengidentifikasi pola intervensi pemuda lintas kasus. Temuan menunjukkan tiga hasil utama. Pertama, pemuda berperan sebagai mediator sosial yang memfasilitasi dialog antarkelompok dan meredakan ketegangan dalam kasus tuduhan penistaan agama, perselisihan antarorganisasi, dan praktik pemakaman yang diperdebatkan. Kedua, inisiatif seperti Sekolah Damai, Pondok Damai, dan forum pemuda lintas iman memperkuat modal sosial bridging dan menciptakan kontak antarkelompok yang terstruktur sehingga mengurangi prasangka. Ketiga, jejaring pemuda berkontribusi pada perubahan kebijakan di tingkat kabupaten, termasuk prosedur perizinan rumah ibadah yang lebih inklusif. Studi ini menegaskan bahwa pemuda merupakan aktor kunci dalam pencegahan konflik berbasis komunitas, bukan sekadar penerima manfaat program moderasi negara. Penelitian ini menyimpulkan bahwa integrasi kontak antarkelompok dan modal sosial merupakan kerangka yang kuat untuk memahami pembangunan perdamaian berbasis pemuda dan merekomendasikan agar pemerintah daerah menginstitusikan partisipasi pemuda dalam mekanisme deteksi dini dan pencegahan konflik